PREPARATION FOR PERFORMANCE APPRAISAL AND PERFORMANCE OF COMMERCIAL BANKS IN MACHAKOS COUNTY- KENYA - Mutindi, Mwanthi Winfred; Nzioki, Susan; Ombuki, Charles (International Journal of Economics, Commerce and Management, 2019)
Preparation for Performance Appraisal (PA) affects performance of commercial banks. When preparing to undertake PA, banks should ensure that; they involve all the stakeholders in setting both organization’s and individual targets; and should be communicated to all members to know what is expected of them. Employees should be trained on PA to reduce rating errors. This study sought to establish how preparation for PA affects performance of commercial banks. The study was conducted in Machakos County in Kenya. Data was collected from 16 commercial banks in the county. Sample size for the study was one hundred and ninety-five (195) respondents. A descriptive survey design was adopted. The research instruments used were questionnaire and interview guide, the former having closed-ended Likert scale questions and the later had guiding questions. Data was analyzed quantitatively and qualitatively using Statistical Package of Social Sciences (SPSS). The study found that there is a positive relationship between Preparation on performance appraisal and performance of commercial banks in Machakos County. The study recommends that organizations should prepare well before conducting employee performance appraisal. Employees should be well trained and involved in setting personal and company goals
Keywords: Preparation, Performance, Stakeholders, Performance Appraisal